Peran Mata Kuliah Pendidikan Anti Korupsi sebagai Upaya Pencegahan Korupsi di Kalangan Mahasiswa PPKn Universitas PGRI Adi Buana Surabaya - Adelya Dwi Putri Johansyah; Bernadetta Budi Lestari; Suhartono (Multiverse: Open Multidisciplinary Journal, 2022)
This study deals with the role of anti-corruption education courses as an effort to prevent corruption among PPKn students at PGRI Adi Buana University Surabaya. This research is a type of research that uses a qualitative approach with analytical descriptive method. Data collection techniques used are interview techniques, questionnaires (questionnaire) and documentation. The objectives of this research are; This study aims to determine the role of anti-corruption education courses as an effort to prevent corruption and to determine the driving and inhibiting factors that affect the implementation of anti-corruption education courses as an effort to prevent corruption among PPKn students at PGRI Adi Buana University Surabaya. The results of the study indicate that anti-corruption education courses act as preventive measures in an effort to reduce and prevent the occurrence of corruption, especially among students. In practice, the driving factor that influences is the urgency of anti-corruption education courses as the basis for students' knowledge of corruption. While the inhibiting factors that influence are the lack of participation by some students who are not actively participating in learning and the student's social environment.